Photocatalytic activity and kinetic study of dye removal over CuFe2O4 under visible light irradiation - Jin Keong, Gan (2014)
The contamination of water resources by industrial effluents containing toxic dyes have serious problem to the human society and environment. The high concentration and higher stability of modern synthetic dyes makes conventional method ineffective for complete degradation of dyes. An advanced oxidation processes (AOPs) is a new technology for treating wastewater based on the generation of hydroxyl radicals (∙OH) by using semiconductor assisted photocatalytic degradation. Organic contaminants attacked repeatedly by ∙OH leads to complete oxidation. Therefore, this work aims to synthesize and characterize copper ferrite, CuFe2O4 photocatalyst which is active under visible light irradiation for dye removal. CuFe2O4 have been prepared by co-precipitation method and undergoes calcination at 300oC for 2 hours. Physicochemical characterization revealed that the catalyst has BET specific surface area of 13.23 m2/g and band gap energy of 1.71 eV. The presence of CuFe2O4 was confirmed via XRD pattern at 2θ of 30.37o, 36.00o, 42.75o and 62.62o respectively. Moreover, crystalline size was in the range of 8.5 to 12.9 nm. The adsorption equilibrium of CuFe2O4 system was found to follow Langmuir adsorption model with adsorption equilibrium constant of 1 x 10-2 L/mg and maximum adsorption capacity of 8.38 mg/g. The effects of catalyst loading and initial concentration of dye were investigated. The photo-degradation of methylene blue (MB) increased with catalyst loading owing to more CuFe2O4 active sites. In contrast, the dye degradation decreased when the initial concentration was increased. This can be explained by the attainment of maximum efficiency by CuFe2O4 photocatalyst. In addition, the Langmuir-Hinshelwood (L-H) models were employed to capture the kinetic trend. Results from the modelling exercise showed that photo-degradation adhered to L-H models and that the reaction constant was 0.131 mg/L.min. The high degradation of MB suggests that CuFe2O4 has promising potential in treating actual dyes-containing wastewater.